Association between childhood parental rearing, sexual partnerships, social support and posttraumatic stress disorders (PTSD) among young HIV-positive MSM. Issue 7 (3rd July 2021) - Luo, Li; Hu, Rong; Cao, Lin; Zhang, Min; Wang, Xia; Xu, Jun
ABSTRACT: We aimed to assess the effect of childhood parental rearing on post-traumatic stress disorder (PTSD) among young HIV-positive men who have sex with men (MSM), as well as the mediation effect of social support on this association. A convenient sampling method and questionnaire-based survey were used to recruit eligible participants from the Wuhan Medical Treatment Center from 20 December 2018 to 28 February 2019. Bivariate analyses were used to investigate the correlations between PTSD and childhood parental rearing, the number of sexual partners and social support. Mediation analyses were used to investigate the mediation of social support. Totally, 142 eligible MSM participated in our study, with prevalence of PTSD being 33.10%. It was found that maternal warmth (M1) and maternal favoring (M5) were positively correlated with social support. Paternal rejection (F5) was positively correlated with PTSD. The effects of M1 and M5 on PTSD were completely mediated by social support. The effects of paternal favoring (F4) and M5 on PTSD were completely mediated by subjective social support, and the effects of F5 and M1 were completely mediated by social support utility. Social support was an important mediator between parental rearing and PTSD.